Profil Kimia Darah sebagai Deteksi Dini Penyakit Degeneratif Pada Kelompok Usia Produktif - Karwiti, Witi; Rezekiyah, Sholeha; Nasrazuhdy, Nasrazuhdy; Lestari, Wuni Sri; Nurhayati, Nurhayati; Asrori, Asrori (Jurnal Kesehatan Komunitas, 2023)
Degenerative diseases are chronic diseases that affect a person's quality of life and productivity. Degenerative diseases include hypertension, asthma, cancer, diabetes mellitus, osteoporosis, and so on. Indonesia's current health problems are influenced by lifestyle, work environment, and stress. The purpose of the study was to determine the differences in laboratory examination results of blood chemistry profiles (blood sugar, cholesterol, uric acid, creatinine, urea, and SGOT levels) at productive age in the Jambi City Health Center Working Area in 2022. The cross-sectional research method with the population is the community in Posbindu in the working area of 3 Puskesmas (KONI, Pakuan Baru, and Putri Ayu) with purposive sampling technique, where the research sample is the Posbindu group who are productive age (16-64 years) which amounted to 140 respondents. The data obtained were then analyzed by independent t-test. The results of laboratory examinations of blood chemistry profile levels, where each variable has high levels, namely 25% prediabetes blood sugar levels, and 10.7% diabetes. Cholesterol 30%, uric acid 20.7%, creatinine 4.3%, ureum 6.4% and SGOT 10%. Conclusion There is a significant difference between the average levels (blood sugar, cholesterol, creatinine, urea, and SGOT) in the productive age group with blood pressure. While uric acid levels have no significant difference because the pvalue> 0.05. Suggestions for the community, it is hoped that they can pay more attention to health conditions by routinely doing Medical check-ups to minimize the occurrence of degenerative diseases at a productive age.